2016
DOI: 10.17352/2455-4634.000020
|View full text |Cite
|
Sign up to set email alerts
|

Position of the Mental Foramen in a Northern Regional Palestinian Population

Abstract: Background: The mental foramen is one of important anatomical features frequently encountered in maxillofacial surgical procedures in premolars area. Its position has been shown to vary according to race. In this study researchers aim to study the position, shape, and appearance of the mental foramen, as seen on panoramic radiographs of Palestinians, and to compare our findings with international values. Materials and methods:A randomly selected panoramic radiographs (368 with 736 sides) from the records of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…The mental foramen position was under the 2nd premolar in the majority of the studied sample. Mohammad et al [ 14 ] found that the commonest site of MF in a sample of a Palestinian population was between the 1st and 2nd premolar, followed by the position under the 2nd premolar. Meanwhile in Jordan [ 15 ], it was found that the most common site was in-between 1st and 2nd premolars.…”
Section: Discussionmentioning
confidence: 99%
“…The mental foramen position was under the 2nd premolar in the majority of the studied sample. Mohammad et al [ 14 ] found that the commonest site of MF in a sample of a Palestinian population was between the 1st and 2nd premolar, followed by the position under the 2nd premolar. Meanwhile in Jordan [ 15 ], it was found that the most common site was in-between 1st and 2nd premolars.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is similar to the study done by different authors in various populations. 1,[12][13][14][15][16][17][18][19][20] Our study revealed score 4 (directly inferior to second PM cusp tip and directly below the second PM apex), to be the second most common score for position of MF i.e., 45.9% on right side and 44.3% on left side. However, in contrast to our findings, studies done by various authors in different population, reported MF to be most commonly present below the apex of second PM (score 4).…”
Section: Most Common Location Of Mfmentioning
confidence: 98%
“…2 It provides sensory innervation to the soft tissues of the chin, lower lip, labial mucosa, lower canines, and incisors. [2][3][4][5] The IAN exits at the mental canal (MeC), and splits into the incisive nerve and the MN. The exit path at the MF is seen in three different patterns; linear or straight, perpendicular or vertical, and anterior loop (AL).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The usual location of the MF is between the apices of the first and second premolars or just below the apex of the second premolar. 3,4 The accurate identification of the MF is essential for diagnostic, clinical, and surgical procedures of the mandible. To untrained eyes, the MF may be mistaken for radiolucent lesions around the apices of the mandibular premolars and lead to misdiagnosis and incorrect interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation